Design and Analysis of a Sensor Interface Circuit - Ahmad Samier Farhan Suhaimi (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
The theory and design of a sensor interface circuit for capacitive sensor is presented. The design used the switch capacitor technique with combination of operational transconductance amplifier (OTA). This technique will cause the circuit design performed based on the ratio between the capacitors. The operational transconductance amplifier (OTA) in this design are used to amplified the input signal. The sensor interface circuit is intended for measure the changes in capacitance between sensor capacitor and reference capacitor, and produce output voltage. All the simulation process is done by using SILVACO gateway software. This study is aimed to investigate the maximum voltage that can be produced by changes the values between sensor capacitor and reference capacitor.